Dicarbonyl Stress and S-Glutathionylation in Cerebrovascular Diseases: A Focus on Cerebral Cavernous Malformations - Cinzia Antognelli; Andrea Perrelli; Tatiana Armeni; Vincenzo Nicola Talesa; Saverio Francesco Retta (MDPI AG, 2020)
Dicarbonyl stress is a dysfunctional state consisting in the abnormal accumulation of reactive α-oxaldehydes leading to increased protein modification. In cells, post-translational changes can also occur through S-glutathionylation, a highly conserved oxidative post-translational modification consisting of the formation of a mixed disulfide between glutathione and a protein cysteine residue. This review recapitulates the main findings supporting a role for dicarbonyl stress and S-glutathionylation in the pathogenesis of cerebrovascular diseases, with specific emphasis on cerebral cavernous malformations (CCM), a vascular disease of proven genetic origin that may give rise to various clinical signs and symptoms at any age, including recurrent headaches, seizures, focal neurological deficits, and intracerebral hemorrhage. A possible interplay between dicarbonyl stress and S-glutathionylation in CCM is also discussed.